Clinical Features and Prognosis of CD20 Negative Aggressive B-Cell Non-Hodgkins Lymphoma. (3rd January 2013) - Gaur, Sumit; Padilla, Osvaldo; Nahleh, Zeina
Abstract : Cluster designation (CD) 20 antigen is expressed on most B-cell lymphomas and serves as a therapeutic target for rituximab. A small minority of aggressive B-cell lymphomas, predominantly plasmablastic variants, do not express CD 20. We systematically reviewed all cases of aggressive B-cell lymphomas diagnosed at our institution over a period of 13 years. Of the 232 cases, 7 did not express CD 20. Five of these were plasmablastic lymphomas while two were unclassifiable B-cell lymphomas. While most of the plasmablastic lymphomas responded to chemotherapy, patients with unclassifiable lymphomas were primarily refractory or relapsed soon after chemotherapy.